2019
DOI: 10.21533/pen.v7i1.406
|View full text |Cite
|
Sign up to set email alerts
|

The impact of internet of things on customer service: A preliminary study

Abstract: The study discuss about internet of Things on serving passengers at Queen Alia International Airport in Amman, Jordan, by knowing its importance and how to minimize its shortcomings in order to improve customer service at the airport. This research allowed us to understand the fears that travelers had, which, if provided, would ensure greater service improvement. Search results show that there is a great impact on Internet things on customer service. The results showed that the variables (safety and scalabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It has become a hot and interesting topic among investors in various fields [15]. IoT is distinguished by non-human intervention, use anywhere, no time limit, reducing cost and time, and a perfect connection because it requires high-speed Internet [42,43]. Fig.…”
Section: A Internet Of Things Overviewmentioning
confidence: 99%
“…It has become a hot and interesting topic among investors in various fields [15]. IoT is distinguished by non-human intervention, use anywhere, no time limit, reducing cost and time, and a perfect connection because it requires high-speed Internet [42,43]. Fig.…”
Section: A Internet Of Things Overviewmentioning
confidence: 99%
“…Customer service representatives are a vital link between customers and service providers (Caplin & Dean, 2015; Joudeh & Dandis, 2018). Studies found that customer service encounters increase customer intention and satisfaction (Nasereddin & Faqir, 2019; Sobolewski & Kopczewski, 2017). However, Ogunnaike, Salau, Adeniyi and Tairat (2014) discovered that not all customers of telecommunications services have access to online information support, especially in developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main objectives of the proposed safety tracking and sensor school bus system are as follows: (1) Ensuring that all the students who got on the bus got off the bus when they reached the schools or their homes. (2) Ensuring that the driver was alerted to the presence of a sleeping student on the bus, and to relieve the parents' anxiety about their children by including them in the system to follow their children.…”
Section: The Proposed Safety Tracking and Sensoring System For Schoolmentioning
confidence: 99%
“…Some of these cameras use in schools for protection for the prevention of accidents, crime, and disasters. Recently, IoT technology has come to be used to solve several issues in transportation, such as at airports, which seek to provide good customer service [2]. In addition, it solve different issues in the educational environment, especially the problem of providing the students' safe transportation to and from their schools every day; a matter over which the parents of the students feel very much concerned.…”
Section: Introductionmentioning
confidence: 99%